2021
DOI: 10.1371/journal.pone.0254984
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Michigan Hand Outcomes Questionnaire in patients with rheumatoid arthritis using Rasch analysis

Abstract: Introduction The Michigan Hand Outcomes Questionnaire (MHQ) is a patient-reported outcome measure previously validated in patients with rheumatoid arthritis (RA) using classical test theory. Rasch analysis is a more rigorous method of questionnaire validation that has not been used to test the psychometric properties of the MHQ in patients with RA. The objective of this study is to evaluate the validity and reliability of the MHQ for measuring outcomes in patients with RA with metacarpophalangeal joint deformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…It is possible that appearance can limit hand function as that both relate to joint deformities. In this case, the 37-item MHQ may be a better option for assessing hand disability in patients with thumb OA because the aesthetics subscale was found to have acceptable fit to the Rasch model in a sample of patients with hand and wrist conditions [ 10 ] and in a sample of patients with rheumatoid arthritis [ 34 ] after modifications were made. Future research would be needed to assess the correlations between the reduced item brief MHQ and the 37-item MHQ in a sample of individuals with thumb OA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that appearance can limit hand function as that both relate to joint deformities. In this case, the 37-item MHQ may be a better option for assessing hand disability in patients with thumb OA because the aesthetics subscale was found to have acceptable fit to the Rasch model in a sample of patients with hand and wrist conditions [ 10 ] and in a sample of patients with rheumatoid arthritis [ 34 ] after modifications were made. Future research would be needed to assess the correlations between the reduced item brief MHQ and the 37-item MHQ in a sample of individuals with thumb OA.…”
Section: Discussionmentioning
confidence: 99%
“…In another Rasch analysis of the 37-item MHQ, three subscales (overall hand function, pain and unilateral activities subscales) were found to be unidimensional and to fit the Rasch model [ 9 ]. On the other hand, a study by Jayaram et al found that with some modifications to the items, the MHQ and all 6 of the subscales fit well to the Rasch model [ 34 ]. When comparing the Rasch analysis findings of the 37-item MHQ [ 9 , 10 , 34 ] and the brief-MHQ, the 37-item MHQ would be more valid and useful for clinicians because the subscale scores would provide valid measures of hand disability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation